3

I have spent about 6 hours now trying to prove this using the Fitch system and I just keep going in circles! Attached is one of the 500 attempts :) I have a feeling it's done fairly simply and straight-forwardly but I'm not too good at understanding the fitch system clearly... One of my attempts Please help!

Updated: Based on the 2 answers provided, I have managed to get here, but stuck again now! (If I use Implication Introduction for the next step, I get: m => q => q)

another attemps

1

You already know p → q. You just need to deduce q → q, enabling you to eliminate the disjunction to conclude q as desired. As: p ˅ q, p → q, q → q Ͱ q

1.|  p → q       : premise
2.|_ m → (p ˅ q) : premise
3.|   |_ m       : assumption
4.|   |  p ˅ q   : conditional elimination (2,3)
5.|   |   |_ q   : assumption
6.|   |  q → q   : conditional introduction (5-5)
7.|   |  q       : disjunction elimination (4,1,6)
8.|  m → q       : conditional introduction (3-7)

The proof writer you are using (Stanford?) should allow this, otherwise you might require the premise to be reiterated into the assumptions scope.


Edit: Ah,I thought this looked familiar.   It is indeed exercise 4-4 of the Standford Logic online course.   There is a "Show Answer" button there, which... does pretty much give the above result.

4

Here's a more elegant solution:

enter image description here

I used http://proofs.openlogicproject.org/ to do the proof.

We have M -> P v Q and we have P -> Q this means that if we get P, we also get Q.

Also our conclusion is a conditional which means conditional introduction is a good way to get that form of conclusion.

So we

  1. begin by assuming M -- since this is the left side of our conditional.
  2. Then we can see we have P v Q by Modus Ponens
  3. Now we want to do a constructive dilemma and get rid of the v
  4. The left horn (P) will give us Q by Modus Ponens
  5. The right horn (Q) is Q, so we just need to repeat it.
  6. This gives us Q at the same level as M.
  7. We can now conclude that if we have M, we get Q.
  • This method is somewhat reminding me of implication graphs. Just like you try all edges and end in the same vertex (Q). – rus9384 Aug 1 '18 at 9:30
3

OH. MY. GOD.

I SOLVED IT!!!!!!!!!!!!!!!!! Thanks so much to do the people who commented, it definitely pointed me in the right direction!!!!

enter image description here

  • 1
    your step 7 is superfluous since you already had that at 1. – virmaior Jul 31 '18 at 15:15
1

m => p|q
So either m => q and it's done, either m => p, and since p => q, m => q.
Given that and the fact that you know how to make a Fitch System (I don't exactly) you can do it easily.

basically, given m at step 3, after step 5 either you assume p and you have q, or you assume q and you have q, so you can say that given m you have q.

I hope I've been clear enough.

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.